Fabrication of Cathode Materials Based on Limn2o4/Cnt and Lini0.5mn1.5o4/Cnt Nanocomposites for Lithium – Ion Batteries Application - Van Le,Thang (2015)
AbstractCarbon nanotubes (CNTs) are a promising candidate material for use in lithium batteries due to 1D tubular structure, high electrical, thermal conductivities, and extremely large surface area. In this work, the MWCNTs were purified by dispersion in a mixture of HNO3 and H2SO4acids. The oxidized-MWCNTs were used as conducting addition to prepare a nanocomposites as high performance cathode material for Li-ion batteries (LIBs). The spinel cathode materials of LiMn2O4 (LMO), doped spinel LiNi0.5Mn1.5O4 (LNMO) were synthesized and characterized via X-rays diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The electrochemical properties of nanocomposites based on LMO/CNTs and LMNO/CNTs were investigated by cyclic voltammetry (CV) as well as electrochemical impedance spectroscopy (EIS). The EIS measurement indicated that the LMO (LNMO)/CNTs nanocomposites showed lower charge transfer resistance (Rct) than that of LMO(LNMO)/ Vulcan carbon materials. In addition, the studied nanocomposites cathodes gave a specific capacity of 145 Ah.kg–1 and 120 Ah.kg–1 for LMO/CNTs (10 wt%) and LNMO/CNTs (10 wt%), respectively, measured at a charge/discharge rate of 0.1C.